(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
There are different kinds of refrigeration system available, have their own merits and demerits. The device is to create a mini refrigerator or cooler using thermoelectric cooler which used peltier technology. The cooler will be light in weight, portable and easy to operate and will keep a constant temperature throughout. This makes it ideal for storing and transporting medicines, vaccines, blood banks and lives human organs also. The device can also used in automobiles with 12V DC supply from the vehicles. The thermoelectric cooler is a new technique which has many advantages over conventional cooling technologies